Tetramethylpyrazine nitrone activates hypoxia-inducible factor and regulates iron homeostasis to improve renal anemia - Cen, Yun; Wang, Peile; Gao, Fangfang; Jing, Mei; Zhang, Zaijun; Yi, Peng; Zhang, Gaoxiao; Sun, Yewei; Wang, Yuqiang (Frontiers in Pharmacology, 2022)
Renal anemia is one of the most common complications of chronic kidney disease and diabetic kidney disease. Given the lack of effective therapy for renal anemia, in this research, we investigated the efficacy and mechanism of action of the novel tetramethylpyrazine nitrone (TBN). Animal models of anemia including the streptozotocin-induced spontaneously hypertensive rats and the cisplatin-induced C57BL/6J mice are established to study the TBN effects on expression of hypoxia-inducible factor and erythropoietin. To explore the mechanism of TBN's therapeutic effect on renal anemia, cobalt chloride (CoCl2) is used in Hep3B/HepG2 cells to simulate a hypoxic environment. TBN is found to increase the expression of HIF-1A and HIF-2A under hypoxic conditions and reverses the reduction of HIFs expression caused by saccharated ferric oxide. TBN also positively regulates the AMPK pathway. TBN stimulates nuclear transcription and translation of erythropoietin by enhancing the stability of HIF-1A expression. TBN has a significant regulatory effect on several major biomarkers of iron homeostasis, including ferritin, ferroportin, and divalent metal transporter-1. In conclusion, TBN regulates the AMPK/mTOR/4E-BP1/HIFs pathway, and activates the hypoxia-inducible factor and regulates iron homeostasis to improve renal anemia.